COLLISIONS BETWEEN EAGLES AND AIRCRAFT: AN INCREASING PROBLEM IN THE AIRPORT ENVIRONMENT - Washburn, Brian E.; Begier, Michael J.; Wright, Sandra E. (DigitalCommons@University of Nebraska - Lincoln, 2015)
Most known fatalities for both Bald Eagles (Haliaeetus leucocephalus) and Golden Eagles (Aquila chrysaetos) are associated with humans (e.g., collisions with vehicles and artificial structures). Notably, the risk of collisions between eagles and aircraft is an increasing problem at civil airports and military airfields. Of the 234 eagle collisions with civil and military aircraft reported to the Federal Aviation Administration, the U.S. Air Force, and the U.S. Navy during 1990–2013, 52% caused damage to the aircraft. During this 23-yr time period, Bald Eagle–aircraft collisions increased by 2200% and Golden Eagle–aircraft collisions increased by 400%. Eagle–aircraft collisions occur primarily during daylight hours (88%) and typically within the vicinity of the airfield itself; 82.6% of the Bald Eagle–aircraft collisions and 81.0% of Golden Eagle strikes occurred when the aircraft was at or below 305 m aboveground level. Although collision with aircraft is a very minor source of mortality for Golden Eagles, increasing and expanding Bald Eagle populations will likely result in more eagle–aircraft collisions. Currently, there are few mitigation tools and techniques available to reduce eagle–aircraft collisions. Development and evaluation of effective, publically acceptable methods of reducing eagle–human conflicts represent important areas for future research.